PENGEMBANGAN DATABASE SISTEM INFORMASI JALUR KERETA BERBASIS WEB MENGGUNAKAN MYSQL - Zidnii Ilma Rimbarawa; Melisa Anggraini Herdi Puspita; Mulyanah Mulyanah (INTECH, 2022)
The database system is a software system that allows users to store a number of data so that users can obtain and maintain information according to their needs. A train line information system can accommodate information such as the time the train arrives at the station, the time the train leaves the station, as well as the sequence of station numbers on the route. For this reason, a railroad information system requires the development of an integrated web-based database that is presented according to criteria. This study aims to find out how to develop a database system for a train line so that it can facilitate the provision of information to passengers. This study uses identification of problems, literature review, system requirements analysis, ERD design and interface design to develop a web-based database system. The research shows that a railway line information system can facilitate passengers to get information about available trains.